Long-term evolution of glomerular filtration rate and proteinuria in single kidney children in a national hospital - Villarreal Giraldo, Ángel Eduardo (2020)
Objetivos: To determine the glomerular filtration rate (GFR) and 24-hour proteinuria among single kidney patients with a minimum 5-year follow-up period. Material y métodos: The medical charts of single kidney attended at Hospital Nacional Edgardo Rebagliati Martins (HNERM) from 2005-2016 were review. Information on 50 patients in whom data on GFR a 24-hour proteinuria was analyzed. Resultados: Median GFR was 109.74 ml/min/1.73m2 (RIQ 86.1-138.75); 22 patients were in the chronic renal disease stage classification I, 2 in chronic renal disease stage classification II and 5 in stage III; 26 patients (52%) had persistent and significant proteinuria, none of these had proteinuria in the nephrotic range. Conclusiones: Single kidney patients present long-term complications such as hyperfiltration and reduction of the GFR.